IMR 665: Management of Audio Visual Records & Archives. Individual Assignment: Article summary / Intan Norhasyimah Abdul Halim - Abd Halim, Intan Norhasyimah (2015)
Article summary: “Cloud Management in Audio Visual Documentation”